DYNAMICS OF VALUE AND MEANING CHARACTERISTICS OF SOCIAL ACTIVITY OF MODERN YOUTH - Irina V Arendachuk (Peoples' Friendship University of Russia (RUDN University), 2018)
The aim of the research presented in the paper is to conduct the comparative study of the value and meaning characteristics of the different types of social activity in the groups of young people that differ in age. The system-diachronic approach developed by R.M. Shamionov is the methodological base of the research. The research was carried out on a sample of young people divided into two groups depending on the stage of age development: young students aged 18-21 (youth, n = 40) and young people aged 22-25 (early adulthood, n = 40). The study of the forms of the manifestation and characteristics of the social activity of the young people was performed with the help of a specially developed questionnaire; its life-purpose characteristics were studied with the help of the Life-Purpose Orientations Test by D.A. Leontiev, The Existence Scale by A. Längle and C. Orgler, the methodology "Life purpose" by O.I. Motkov. Value orientations were studied using the methods "Diagnostics of the real structure of value orientations of the personality" by S.S. Bubnova and "Personality Profile" by Sh. Schwartz. It was revealed that leisure, network and educational spheres dominate in the structure of young people's social activity, and and in the case of students it is also the spiritual sphere. It was found out that life-purpose and existential orientations define the leisure, civic, socio-economic and educational activity at the age of 18-21; the system of values and life orientations aimed at supporting other people determine the altruistic and religious types of activity. At the age of 22-25, the focus on personal attitude toward one's own life, finding the meaning in life, the orientation towards social relations and traditions defines the manifestation of altruistic, leisure, social, political, network, civic, educational, spiritual and religious types of activity. The socio-economic activity is determined by the focus on the implementation of life purposes and the orientation towards hedonism; the same focus reduces the degree of the manifestation of protest activity. In the dynamics of the young people's age development, the tendency of decreasing the importance of life-purpose characteristics of social activity and increasing the significance of the value orientations and the person's orientation toward the implementation of life purposes is revealed.